By heresies distressed [compact disc, unabridged] - Weber, David, 1952- (Weber, David, 1952- Safehold series., 2009)
In the marriage of Queen Sharleyan of Chisholm to King Cayleb of Charis, the Kingdoms of Charis and Chisholm on the planet Safehold have united as one empire, standing for human freedom. As Sharleyan and Cayleb fall deeply in love, the two band together with their unified empire to fight against the corrupt Church and its Group of Four. Unbeknownst to Sharleyan, Cayleb possesses a slew of secrets about the history of Safehold, secrets that may endanger his beloved and their cause.